Teaching Material for Human Literacy: Multicultural-Charged Explanatory Text for Reducing Social Conﬂict - Zulaeha, Ida; Wagiran, Wagiran; Yuniawan , Tomi (KnE Social Sciences, 2019)
Languageisasocialphenomenonthatisnotseparatefromthespeakercommunity.The existence of text represents the speaker in various interaction functions. This research was conducted to produce Indonesian language material with multicultural content to reduce social conﬂict in the younger generation and optimize the implementation of the 2013 curriculum. The subject of this research is teaching materials for explanatory textsinwhichtherearerealmulticulturalvaluesinsociety.Researchdatawascollected through a focus group discussion between researchers and a number of Indonesian languageteachers.Thedevelopmentofafactualmodelwascarriedoutbyresearchers with a team of Indonesian Language lecturers with reference to the ﬁndings of the theoretical teaching material model. Indonesian teaching materials with multicultural content in reducing social conﬂict in the younger generation are developed in aspects of content, language, and presentation. The diversity of the Indonesian nation on the one hand has a positive value, but on the other hand it stores negative values that are unavoidable as innovations in the aspect of content. The diversity of the Indonesian peopleturnedouttobevulnerabletoactsofviolenceduetosocialconﬂict,especially intheyoungergeneration.Multiculturalawarenessisneededontheyounggeneration of Indonesia through learning Indonesian as a form of humanist literacy. Keywords: humanist literacy teaching material, multicultural explanatory text, social conflict